Incretin Effect and Glucagon Responses to Oral and Intravenous Glucose in Patients With Maturity-Onset Diabetes of the Young—Type 2 and Type 3 - Østoft, Signe H.; Bagger, Jonatan I.; Hansen, Torben; Pedersen, Oluf; Holst, Jens J.; Knop, Filip K.; Vilsbøll, Tina (Diabetes (New York, N.Y.), 2014)
Maturity-onset diabetes of the young (MODY) is a clinically and genetically heterogeneous subgroup of nonautoimmune diabetes, constituting 1–2% of all diabetes. Because little is known about incretin function in patients with MODY, we studied the incretin effect and hormone responses to oral and intravenous glucose loads in patients with glucokinase (GCK)-diabetes (MODY2) and hepatocyte nuclear factor 1α (HNF1A)-diabetes (MODY3), respectively, and in matched healthy control subjects. Both MODY groups exhibited glucose intolerance after oral glucose (most pronounced in patients with HNF1A-diabetes), but only patients with HNF1A-diabetes had impaired incretin effect and inappropriate glucagon responses to OGTT. Both groups of patients with diabetes showed normal suppression of glucagon in response to intravenous glucose. Thus, HNF1A-diabetes, similar to type 2 diabetes, is characterized by an impaired incretin effect and inappropriate glucagon responses, whereas incretin effect and glucagon response to oral glucose remain unaffected in GCK-diabetes, reflecting important pathogenetic differences between the two MODY forms.